Wind Tunnel Studies on the Prevention of Particle Accumulation Onto the Bogie of High-Speed Train - Liu, Yusheng; Li, Guang; Zhang, Jie (Frontiers in Earth Science, 2022)
When high-speed train runs in the environment with a large number of airborne particles, these particles may accumulate on the bogie of the train, which will further challenge the normal operation of the bogie and reduce the riding comfort and train safety. In order to prevent particles entering into the bogie area, different protective devices around the bogie are used. However, up to present, the systematical analysis on the protective effects of diverse protective measures against different types of particles are still very limited. In this study, with the widely-used shirt boards and spoilers as protective devices, the airborne particle transport processes around the bogie were simulated in the wind tunnel Lab. Three kinds of typical particles, including artificial snow particle, wheat bran (substitute of snowflake) and sieved soil, were chosen to represent different airborne particles under real conditions. Three evolution indexes, including the relative reduction ratio of artificial snow particles, the relative particle flux reduction ratio of fine wheat bran, and the relative concentration reduction ratio of fine sieve soil particles, were used to assess their protective effects. Results showed that the combination of short-skirt board and straight triangular spoiler (i.e. in A5 case, the straight triangle spoilers installed at the front and rear ends of the train bogie, and the short-skirt boards installed on both sides of the train bogie) was the best protection with the studied three particles. The relative reduction ratio of the average snow mass in this case was 75.59%, the relative reduction ratio of the flux in the level of fine wheat bran exceeded 78%, and the relative reduction ratio of the fine soil particle concentration was more than 96%.